Performance-based earthquake evaluation of a full-scale petrochemical piping system. (January 2015) - Bursi, Oreste S.; Reza, Md S.; Abbiati, Giuseppe; Paolacci, Fabrizio
Abstract: Assessment of seismic vulnerability of industrial petrochemical and oil & gas piping systems can be performed, beyond analytical tools, through experimental testing as well. Along this line, this paper describes an experimental test campaign carried out on a full-scale piping system in order to assess its seismic behaviour. In particular, a typical industrial piping system, containing several critical components, such as elbows, a bolted flange joint and a Tee joint, was tested under different levels of realistic earthquake loading. They corresponded to serviceability and ultimate limit states for support structures as suggested by modern performance-based earthquake engineering standards. The so called hybrid simulation techniques namely, pseudo-dynamic and real time testing with dynamic substructuring, were adopted to perform seismic tests. Experimental results displayed a favourable performance of the piping system and its components; they remained below their yielding, allowable stress and allowable strain limits without any leakage even at the Near Collapse Limit State condition for the support structure. Moreover, the favourable comparison between experimental and numerical results, proved the validity of the proposed hybrid techniques alternative to shaking table tests. Highlights: A petrochemical piping system was tested under seismic loading. FE modelling and analysis of the piping system were performed. Pseudo-dynamic and real-time tests were conducted. The piping system and components remained below yield limits. A favourable agreement was found between experimental and numerical results.